Clinical presentation of Parkinson’s disease 1 - Factor, Stewart A. (Henry Stewart Talks, 2024)
Parkinson’s disease (PD), Epidemiology of PD, Clinical phases of PD, REM behavior disorder (RBD), Motor features Types of tremor in PD, Akinesia and bradykinesia Postural instability and gait disorder